The changing role of property law : rights, values and concepts - Nordveit, Ernst (Edward Elgar Publishing, 2023)
"This timely book analyses the most significant contemporary developments and trends in property law, including the concept of property rights, the role of property law and property rights in society, and the values they enhance. It examines the effect of property rights on social, economic and cultural development and vice versa, considering the impact of phenomena such as technological innovation, digitalisation and blockchain technology, changes in social and economic organisation, and globalisation. Featuring contributions from top international scholars in the field, chapters explain the variety of property rights found in most legal systems and how these develop in relation to social needs and available resources. The book discusses the current transition of property from mainly physical objects to intangible values in the form of, for example, intellectual property rights, and the impacts this is having on the law, democracy and free speech. Other prominent issues tackled by the book include the organisation of registries for property rights, models for managing public property, and the influence of new property forms on family and inheritance law. An essential read for scholars and students of property law, including intellectual property, the book will also be of interest to those working in family law, law and technology and commercial law whose research intersects with property rights"--